The, Of, In Punitive Policy In The Field Of Penal Legislation In Robbery Cases In The Basic Court In Gjilan – Branch In Vitia During The Period 2013-2017: Some of the forms of implementation of punitive policy against robbery in the area of criminal legislation - Aliu, Albana (Acta Universitatis Danubius. Juridica, 2020)
Criminal offense of robbery has become a constant phenomenon in our country, as an act that violates and undermines the property values of society, which are guaranteed by international conventions, as well as with local laws. I have considered reasonable to survey, analyze and observate this issue, so we can look closely at the implementation of the punitive policy, with a special approach to detecting and prosecuting the perpetrators of the criminal offense of robbery, addressing the work done by the judiciary bodies, especially the police and prosecution office, therefore, case studying and analyzing the work of judicary bodies contributes in recognizing the steps taken in these cases and prevent future similar cases of robbery.